BUILDING BRIDGES: THE INTEGRATIVE POWER OF PUBLIC RELATIONS IN SHAPING AZAD UNIVERSITY’S SOCIAL RESPONSIBILITY FRAMEWORK - Hosseini , Mohammad Reza; Zadeh, Sara Farahani (International Journal of Management and Allied Research (IJMAR), 2024)
Organizations emerge in response to the overarching and societal requirements, shaped by the collective and social needs of the public or specific groups, often articulated by the visionary founders. This intrinsic connection between organizations and the broader socio-economic fabric underscores the dynamic interplay between general needs, social dynamics, and the deliberate initiatives of organizational creators. Understanding this symbiotic relationship is pivotal for navigating the complexities of organizational development and sustainability. This paper delves into the fundamental premise that organizations are established to fulfill specific societal demands, whether arising from a widespread recognition of public needs or the visionary aspirations of their founders. By exploring the genesis of organizational entities, we gain insights into the intricate balance between the evolving demands of the public sphere and the intentional initiatives that lead to the formation of diverse organizational structures.